Pemberdayaan Masyarakat Melalui Inovasi Pembuatan Paving Block Dari Sampah Plastik Sebagai Upaya Peningkatan PHBS di Kelurahan Wuring Kabupaten Sikka - Sisilia Wati Dua Wida, Agustina; Kaidu, Triapriono; Chotimah, Nur; Dikson, Melkias; Rangga, Yohanes Paulus Pati Rangga (Politeknik Negeri Jember, 2026)
Waste is one of the problems in Indonesia that can have a negative impact on both the environment and public health. The increasing problem of plastic waste management in coastal areas, especially in Wuring Village, Sikka Regency, is a serious challenge to environmental cleanliness and the implementation of Clean and Healthy Living Behavior (PHBS). This community service activity aims to empower the community through training and mentoring in the innovation of making paving blocks from plastic waste. The implementation method includes education about PHBS, technical training in managing plastic waste into building materials (paving blocks), and the formation of community self-help groups as implementers of the follow-up program. The results show an increase in community knowledge and skills in managing waste productively and increasing public awareness of the importance of a clean environment. This innovation not only supports the reduction of plastic waste, but also opens up local economic opportunities. Thus, this program makes a real contribution to improving PHBS while encouraging the community to be independent in creating a healthy and productive environment.